Effects of Spiritual Mindfulness on Spiritual Self Reliance and Medication Adherence in Patients with Schizophrenia - Meidiana Dwidiyanti; Sri Padma Sari; Diyan Yulia Wijayanti; Hasanah Eka Wahyu Ningsih; Reza Indra Wiguna; Akhmad Yanuar Fahmi Pamungkas; Badrul Munif (Jurnal Ilmu Keperawatan Jiwa, 2020)
Mental health problems have been a concern in all countries throughout the world. Patients with schizophrenia tend to have low spiritual self-reliance and medication adherence, resulting in an increasing number of hospitalizations. Spiritual interventions, for example, spiritual mindfulness, are evident to improve patients’ spiritual self-reliance and self-awareness to adhere to medication. This study aimed to determine the effects of Spiritual Mindfulness on spiritual self-reliance and medication adherence in patients with schizophrenia. The present study used a pre-posttest quasi-experimental design without a control group. The samples were 45 patients with schizophrenia at a psychiatric hospital in Semarang, Indonesia. Spiritual Mindfulness was given to the patients for six meetings. The data were collected using the questionnaires of DAI (Drug Attitude Inventory) and NAMA (Nursing Assessment of Medication Acceptance) and analyzed using a t-test or mean/median difference test or delta analysis. The results showed that Spiritual Mindfulness affected the spiritual self-reliance of schizophrenic patients with a p-value of 0.001. Spiritual Mindfulness also affected drug-taking behaviors (p=0.027) and drug-taking acceptance (p=0.000). Spiritual Mindfulness gave effects on the level of self-efficacy of spiritual self-reliance and medication adherence in patients with schizophrenia.